VARIASI BAHASA STIKER SEPEDA MOTOR DI KOTA MOJOKERTO SERTA RELEVANSI DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP - Peny Puji Astuti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This research to describe variation of language, factors that influence the use of language variations on motorcycle stickers in the city of Mojokerto and the relevance of the results in Indonesian language learning in junior high schools. This type of research uses descriptive qualitative. The research subjects used were stickers on motorbikes in the area of ??Mojokerto city. The area of ??this research is Mojokerto Square, Majapahit Street and Benteng Pancasila Street area. Triangulation of method and theory techniques is used by researchers to test the credibility of the data. The amount of data in this study there were 27 motorcycle stickers. Based on the results of data analysis obtained the results of the study that variations in language used on motorcycle stickers in the city of Mojokerto found variations in language based on speakers, variations in language based on usage and variations in language based on formality. Language variations in terms of speakers found are dialects and sociology. Language variations in terms of usage found are based on usage in religious fields. Language variations in terms of formality are found, namely consultative,casual, and intimate. Factors that influence the use of language variations include linguistic factors and nonlinguistic factors. The results of the study, which are adapted to the basic competencies and interview results, show the relevance of the results of the study with Indonesian language learning in junior high schools, especially slogan material. Basic competencies relevant to competency 3.4. Examine the presentation and linguistic patterns of ad text, slogans, or posters (which make proud and motivating) from various sources that are read and heard. Keyword: variation of language, stickers, Indonesian language learning